Development and implementation strategies of a nurse-led symptom self-management program in outpatient cancer centres: The Symptom Navi© Programme. (February 2020) - Bana, Marika; Ribi, Karin; Kropf-Staub, Susanne; Näf, Ernst; Schramm, Monique Sailer; Zürcher-Florin, Sabin; Peters, Solange; Eicher, Manuela
Abstract: Purpose: The Symptom Navi© Programme (SN©P) is a structured nurse-led intervention supporting symptom self-management in cancer patients. We describe the development and evaluation of the intervention, implementation strategy, and the evaluation of nurse training for the Symptom Navi© Pilot Study. Methods: The intervention was developed using multiple methods (e.g. literature synthesis, focus groups) to produce SN©P information leaflets (SN©Flyers in French and German) and standardised training for nurses to deliver semi-structured consultations. We evaluated the SN©P using online surveys, focus groups, interviews, and the Item-Content Validity Index (I-CVI). Nurse training was evaluated in relation to content, acceptability, and confidence in implementing the SN©P. We examined the association between scored on the Work-related Sense of Coherence (Work-SoC) scale and nurses' confidence in implementing the SN©P. Thematic analysis was used to analyse qualitative data. Quantitative data was descriptively analysed and the Kendall Tau test was employed for correlations. Results: Patients and health care professionals confirmed that SN©Flyers and semi-structured consultations facilitated symptom self-management. Nurses considered training content/format acceptable and appropriate and felt confident in implementing the SN©P. Overall Work-SoC scores were correlated with nurses' confidence in implementing the SN©P (rπ = .47, p = .04). Conclusions: Health care professionals and cancer patients perceived the SN©P as a useful support. Successful implementation of the SN©P depends on centre-specific factors including time, resources and workflow. Clinical trial registry: NCT03649984 and SNCTP000002381. Highlights: Standardised symptom self-management support is insufficiently implemented. The Symptom Navi© Programme showed excellent face validity, clarity and utility. Nurse training facilitated the implementation of the program into daily routines. Nurses' workload might be a barrier for applying the program in daily routines.